2009
DOI: 10.1007/s11703-009-0058-2
|View full text |Cite
|
Sign up to set email alerts
|

Studies on induction of chlorophyll mutations in soybean, Glycine max (L.) Merrill

Abstract: The phenotypic response of two soybean cultivars to a chemical mutagen (ethyl methane sulphonate, EMS), physical mutagen (gamma rays) and their combinations were studied in M 1 and M 2 generations and the frequency and spectrum of chlorophyll mutations were worked out. Combined treatment was found to be more effective in inducing chlorophyll mutations compared to individual treatments of gamma rays and EMS in both the cultivars. As far as the spectrum of chlorophyll mutations is concerned, a wider spectrum in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
(3 reference statements)
3
9
0
Order By: Relevance
“…The chemical mutagens induced more variability in LH90-54, whereas the physical mutagen (gamma rays) was found more effective in LH89-48. Similar observations with regard to the mutagens and mutagenic treatments have been reported earlier in lentil (Sarker and Sharma, 1987), chickpea (Pathania and Sood, 2006), green gram (Singh and Rao, 2007) and soybean (Kartika and Subba Lakshmi, 2006;Khan and Tyagi, 2009). …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The chemical mutagens induced more variability in LH90-54, whereas the physical mutagen (gamma rays) was found more effective in LH89-48. Similar observations with regard to the mutagens and mutagenic treatments have been reported earlier in lentil (Sarker and Sharma, 1987), chickpea (Pathania and Sood, 2006), green gram (Singh and Rao, 2007) and soybean (Kartika and Subba Lakshmi, 2006;Khan and Tyagi, 2009). …”
Section: Resultssupporting
confidence: 85%
“…LH89-48. The incidence of higher mutation induction by alkylating agents, particularly EMS, is due to their higher alkylation ability affecting gene molecule directly in lentil (Sarker and Sharma, 1987;Sharma, 1999, 2001), Vicia faba (Bhat et al, 2007), soybean (Kartika and Subba Lakshmi, 2006;Khan and Tyagi, 2009), chickpea (Khan et al, 2005;Pathania and Sood, 2006) and green gram (Velu et al, 2008). EMS has also been reported to induce higher frequency of mutations than SA in lentil (Solanki and Phogat, 2005) and chickpea (Khan et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Paul and Singh (2002) reported 0.8% of chlorophyll mutants in lentils using 100 and 150 Gy. The frequency of chlorophyll mutation was observed as 1.21% and 2.42% in two varieties of soybean at 150 Gy (Khan and Tyagi, 2009). In cluster bean, Bhosle and Kothekar (2010) recorded 1.66%, 2.21% and 2.61% of chlorophyll mutations at 50, 100 and 150 Gy, respectively.…”
mentioning
confidence: 93%
“…Numerous authors have so for reported the incidence of different types of chlorophyll mutations such as albina, xantha, chlorina, viridis, virescent, tigrina, etc. in M 2 generation following mutagenic treatments (Waghmare 2001;Toker and Cagirgan 2004;Yamaguchi et al 2006;Khan and Tyagi 2009;Arulbalachandran and Mullainathan 2009;Wani et al 2011b;Girija and Dhanavel 2013a). Chemical mutagens induce higher frequency of chlorophyll mutations as compared to radiations in chickpea (Kharkwal 1998b) and grasspea (Waghmare and Mehra 2001).…”
Section: Chlorophyll Mutations Effectiveness and Efficiency Of Mutagensmentioning
confidence: 99%